Antioxidants from three Swietenia Species (Meliaceae) (2016)
ABSTRACT: The genus Swietenia (Meliaceae) has a wide variety of secondary metabolites with reported antioxidant activity, such as flavonoids and limonoids. In the present study, the antioxidant capacity, along with the phenol and flavonoid contents of the leaf extracts of three species of this genus: Swietenia mahagoni, Swietenia macrophylla, and Swietenia humilis were evaluated. The antioxidant activity was determined by the 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2'-azino-bis-(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS), ferric reducing/antioxidant power (FRAP), and oxygen radical absorbance capacity (ORAC) methods. The results showed that the three species had significant antioxidant activity and substantial contents of phenolic compounds and flavonoids. The species S. macrophylla was the most effective, and compounds with recognized antioxidant capability were detected by gas chromatography coupled with mass spectrometry (GC-MS). Catechin was the most abundant constituent in the active fractions, and was confirmed and quantified by high performance liquid chromatography (HPLC).